2010
DOI: 10.4067/s0718-16202010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and control of runoff and soil erosion on avocado orchards on ridges along steep-hillslopes

Abstract: -1 of soil erosion during the first year after ridges were built, while mitigation measures can reduce erosion in 90%. Adult orchard showed the largest runoff, which probably is due to the effect of a high and about constant soil moisture during irrigation period and smaller infiltration capacity of eroded soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…The interception of rainfall by groundcovers dissipates the impact of raindrops on the soil surface, ultimately reducing runoff and erosion ). We observed a significant reduction in runoff and erosion in both groundcover treatments compared to the bare soil treatment, and similar observations were reported by Youlton et al (2010) and Francia Martinez et al (2006), in avocado and olive orchards under different groundcover treatments.…”
Section: Mitigation Of Nutrient Lossessupporting
confidence: 92%
See 2 more Smart Citations
“…The interception of rainfall by groundcovers dissipates the impact of raindrops on the soil surface, ultimately reducing runoff and erosion ). We observed a significant reduction in runoff and erosion in both groundcover treatments compared to the bare soil treatment, and similar observations were reported by Youlton et al (2010) and Francia Martinez et al (2006), in avocado and olive orchards under different groundcover treatments.…”
Section: Mitigation Of Nutrient Lossessupporting
confidence: 92%
“…Previous studies have shown that groundcovers can provide runoff and soil erosion control in perennial fruit plantings on hillsides Garcia-Orenes et al 2009;Gomez et al 2003;Martinez Raya et al 2006;Youlton et al 2010). The interception of rainfall by groundcovers dissipates the impact of raindrops on the soil surface, ultimately reducing runoff and erosion ).…”
Section: Mitigation Of Nutrient Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some shrublands could be negatively affected by grazing activities and transformed into grasslands. Moreover, the strong promotion of agriculture through multiple financial and regulatory instruments has led to agricultural development on slopes, especially of avocado trees and vineyards for wine production, in the Central Valley [ 72 ]. In addition, the increase in forests could be related to methodological improvements made to the cadasters [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason why the topsoil layer of Andosols under avocado orchards has greater mechanical resistance to penetration may be linked to compaction because of transit of motorized farm vehicles (frequency of usage) as well as trampling by laborers during weeding, pruning, agrochemical application, and harvesting activities, among other possible causes. Because soil compaction reduces pore size, hardening of the topsoil may reduce water infiltration and induce an earlier start of superficial runoff at moderate intensities of rainfall (Kozlowski, 1999;Youlton et al, 2010). A study in Malaysia showed that the conversion of secondary tropical peat swamp forest to oil palm plantation significantly increased soil bulk density and soil strength (Firdaus et al, 2010).…”
Section: Physical Propertiesmentioning
confidence: 99%